Degradable poly(methyl terephthalate) and methods of making and using the same

CN122897973APending Publication Date: 2026-10-13HUBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611236963.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0006]本发明目的在于提供一种可降解聚对苯二甲酸甲二酯及其制备方法和应用,有效解决了传统聚酯化学稳定性过强、自然环境中难以降解、易造成长期白色污染的问题

Benefits of technology

本发明通过分子结构设计,将传统聚对苯二甲酸乙二酯重复单元中的乙撑替换为亚甲基,制得聚对苯二甲酸甲二酯,从分子根源赋予聚酯材料内在可降解性能,有效解决了传统聚酯化学稳定性过强、自然环境中难以降解、易造成长期白色污染的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897973A_ABST
    Figure CN122897973A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of polyester material degradation modification, and particularly relates to a degradable poly-methyl terephthalate as well as a preparation method and application thereof. In the present application, the ethylene in the repeating unit of poly-ethylene terephthalate is replaced by methylene, the main chain contains -O-CH2-O-methyl ester structure, and the number average polymerization degree is 11-14. The poly-methyl terephthalate is prepared from terephthalic acid and dibromomethane under the action of an alkaline catalyst and a phase transfer catalyst through solution polycondensation, and the reaction condition is mild and the product is pure. When the polyester is hydrolyzed in alkaline, the methyl ester unit can undergo intramolecular rearrangement and release formaldehyde, and the degradation is efficiently carried out from the thermodynamic driving, and the degradation rate under mild conditions is much higher than that of traditional polyesters; the glass transition temperature of the polyester is up to 107 DEG C, the 5% thermal weight loss temperature is higher than 300 DEG C, and the polyester has good thermal stability and intrinsic degradability, and can be used for disposable packaging, degradable fibers, agricultural films and composite degradable matrix, and realizes lossless recovery of the reinforcing components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polyester material degradation and modification technology, specifically relating to a biodegradable polyethylene terephthalate, its preparation method, and its application. Background Technology

[0002] Polyethylene terephthalate (PET) is a type of high-performance thermoplastic polyester. Due to its excellent mechanical strength, thermal stability, chemical stability and processability, it is widely used in synthetic fibers, food packaging (beverage bottles), engineering plastics and films.

[0003] However, the large-scale use of PET has also brought serious environmental problems and resource waste. From the perspective of molecular structure, PET molecular chains are highly regular and crystalline, and the benzene ring and ester group can form a strong conjugated system, giving it extremely strong chemical inertness and making it very difficult to degrade in the natural environment. Waste PET products can remain in soil, rivers, and marine environments for hundreds of years without decomposing, causing continuous "white pollution" and resulting in the waste of a large amount of polymer resources.

[0004] Currently, PET recycling methods mainly fall into two categories: mechanical recycling and chemical recycling. Mechanical recycling primarily reuses waste PET through melting and reprocessing. However, this process leads to thermal oxidative degradation of the PET molecular chains, resulting in a decline in the material's mechanical properties, constituting a downgraded utilization that cannot restore the material to its virgin performance level. Chemical recycling, on the other hand, breaks down PET macromolecules into monomer raw materials through depolymerization reactions. This mainly includes technologies such as methanololysis, hydrolysis, and glycolysis. While theoretically, monomer regeneration can be achieved, existing processes generally suffer from stringent reaction conditions. Effective depolymerization typically requires high temperatures, high pressures, strong acids / bases, or special catalysts, resulting in high energy consumption and complex depolymerization products with cumbersome subsequent separation and purification processes, limiting its large-scale industrial application. For example, alkaline hydrolysis of PET requires temperatures above 100°C and high-concentration alkaline solutions for several hours or even longer to achieve a high degradation conversion rate, resulting in low degradation efficiency and demanding processing conditions.

[0005] Therefore, developing novel PET alternatives through molecular structure design, enabling them to maintain good performance while possessing inherent degradability and achieving efficient degradation under mild conditions, fundamentally solving the problem of material environmental durability, has significant research value and social significance. Summary of the Invention

[0006] The purpose of this invention is to provide a biodegradable polyethylene terephthalate, its preparation method, and its application, which effectively solves the problems of traditional polyesters being too chemically stable, difficult to degrade in the natural environment, and prone to causing long-term white pollution.

[0007] The objective of this invention is achieved through the following technical solution: The present invention provides a biodegradable polyethylene terephthalate (PET), wherein the repeating unit of the PET is composed of terephthalic acid structural units and methylene groups connected by ester bonds, and the main molecular chain contains -O-CH2-O-methyldiester structural units.

[0008] Furthermore, the number-average degree of polymerization of the polymethyl terephthalate is 11-14.

[0009] The present invention also provides a method for preparing the biodegradable polymethyl terephthalate, comprising the step of carrying out a solution polycondensation reaction of terephthalic acid and dibromomethane in an organic solvent under the combined action of an alkaline catalyst and a phase transfer catalyst.

[0010] Furthermore, the specific steps include the following: (1) Heat the temperature to 80°C to melt the alkaline catalyst, and add terephthalic acid to react; (2) Add dibromomethane, organic solvent and phase transfer catalyst, and carry out polycondensation reaction at 90~120℃ under inert atmosphere and mechanical stirring for 12~24 hours; (3) After the reaction is complete, the reaction solution is added to a settling agent to precipitate the precipitate. After filtration, washing and drying, the target product is obtained.

[0011] Further, in step (1), the molar ratio of terephthalic acid to alkaline catalyst is 1:(2.0~2.2), and the alkaline catalyst is tetramethylammonium hydroxide pentahydrate; in step (2), the molar ratio of terephthalic acid, dibromomethane, and phase transfer catalyst is 1:(1.0~1.5):(0.05~0.2), and the phase transfer catalyst is triethylbenzylammonium chloride or tetrabutylammonium bromide, and the organic solvent is nitrobenzene; in step (3), the precipitant is methanol, ethanol, or an aqueous solution thereof.

[0012] The present invention also provides an application of the biodegradable polyethylene terephthalate (PET), the application of which includes utilizing the acid and alkali degradability of PET to prepare it into biodegradable polymer products, or achieving the harmless disposal and component recovery of PET-containing materials through degradation treatment.

[0013] Furthermore, the biodegradable polymer products include disposable packaging materials, biodegradable fibers, and agricultural films.

[0014] Furthermore, the polymethyl terephthalate is used as a biodegradable matrix resin in the composite material. By degrading the matrix resin, the functional components in the composite material can be recovered without damage.

[0015] Furthermore, the degradation treatment is carried out in an alkaline environment; the alkaline environment is an aqueous solution of sodium hydroxide or potassium hydroxide with a concentration of 0.5~5.0M, and the degradation temperature is 25~100℃.

[0016] Furthermore, the recovered functional components in the composite material are reinforcing fibers or fillers.

[0017] The beneficial effects of this invention are as follows: This invention, through molecular structure design, replaces the ethylene in the repeating unit of traditional polyethylene terephthalate with methylene to obtain polyethylene terephthalate, thereby endowing polyester materials with inherent degradability from the molecular level. This effectively solves the problems of traditional polyesters being too chemically stable, difficult to degrade in the natural environment, and prone to causing long-term white pollution.

[0018] This invention uses terephthalic acid and dibromomethane as direct raw materials for polymerization. Dibromomethane is a cheap and readily available general chemical raw material, which can effectively reduce monomer costs and synthesis inputs. At the same time, its structural characteristics provide a structural basis for the generation of escape gases during the subsequent degradation process, providing a stable thermodynamic driving force for the degradation reaction.

[0019] The solution polycondensation reaction of the present invention can be carried out smoothly under mild conditions of normal pressure and 90~120°C, without the need for the high temperature above 250°C and the high vacuum environment below 100Pa required by the traditional polyethylene terephthalate production process. This greatly reduces the reaction energy consumption and equipment configuration requirements, and the process operation is simple, making it easier to realize industrial scale-up production.

[0020] This invention introduces a phase transfer catalyst into the polymerization system, which can effectively enhance the mass transfer and reaction process at the two-phase interface, shorten the polycondensation reaction time to 12-24 hours, and obtain polyester products with suitable degree of polymerization under mild reaction conditions, effectively improving the overall synthesis efficiency and production pace.

[0021] The polymethyl terephthalate prepared by this invention has a unique degradation mechanism. During alkaline hydrolysis, the unique methyl terephthalate structural units in its main molecular chain can undergo intramolecular rearrangement and release formaldehyde gas. As a gaseous product, formaldehyde will continuously escape from the reaction system, constantly pushing the hydrolysis equilibrium towards the product formation direction, thus ensuring the efficient and thorough degradation reaction from a thermodynamic perspective.

[0022] The polyethylene terephthalate (PET) prepared by this invention can achieve efficient degradation under mild conditions. Tests show that after reacting for 5 hours in a 3.0M sodium hydroxide aqueous solution at 50°C, its mass loss rate can reach 98.1%, which is much higher than the 23.7% degradation rate of traditional polyethylene terephthalate under the same reaction conditions. The improvement in degradation efficiency is very significant.

[0023] The polyethylene terephthalate (PET) prepared by this invention has superior heat resistance properties, with a glass transition temperature of up to 107°C, which is significantly higher than the glass transition temperature of 78°C for traditional polyethylene terephthalate (PET). This reflects that the polyester molecular chain has higher chain rigidity, and the material has greater advantages in high-temperature dimensional stability and operating temperature range.

[0024] The polymethyl terephthalate obtained by this invention still maintains good thermal stability, with a 5% thermal weight loss temperature exceeding 300°C. This fully meets the conventional processing and daily use temperature requirements of general plastics, fiber materials, and composite matrix resins, achieving both biodegradability and basic material performance.

[0025] The polymethyl terephthalate prepared by this invention has a wide range of applications. It can be directly used to prepare environmentally friendly products such as disposable packaging materials, biodegradable fibers, and agricultural films. After the products reach the end of their service life, they can be fully degraded by simple alkaline treatment, which can effectively reduce the environmental burden caused by waste plastic products.

[0026] The polymethyl terephthalate prepared by this invention can be used as a biodegradable matrix resin in fiber-reinforced composite materials. After the composite material reaches the end of its service life, the polyester matrix can be fully degraded through mild alkaline treatment, thereby realizing the high-value non-destructive recycling and reuse of the internal reinforcing fibers or fillers, providing a feasible solution to the problem of composite material recycling. Attached Figure Description

[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 The solid-state carbon NMR spectrum of polymethyl terephthalate (PMT) prepared in Example 1 of this invention (…) Figure 1 (a) and the specific chemical structure diagram ( Figure 1 (b) is used to characterize the chemical structure and purity of PMT products.

[0029] Figure 2 The ¹H NMR spectra of the synthesis system of Comparative Example 1 of this invention are shown below; where (a,d) are the ¹H NMR spectra of the 1,2-dibromoethane monomer, (b,e) are the ¹H NMR spectra of the terephthalic acid monomer, and (c,f) are the ¹H NMR spectra of the PET polyester synthesized in Comparative Example 1, used to verify the chemical structure and product purity of the PET polyester.

[0030] Figure 3 The synthesis system of Comparative Example 1 of this invention 13 C10 NMR spectra; where (a,d) are the carbon spectra of 1,2-dibromoethane monomer, (b,e) are the carbon spectra of terephthalic acid monomer, and (c,f) are the carbon spectra of PET polyester synthesized in Comparative Example 1, used to further verify the molecular chain structure of PET polyester.

[0031] Figure 4 In Experimental Example 3 of this invention, 20℃•min -1 Differential scanning calorimetry (DSC) temperature spectra of PMT synthesized in Example 1 and PET synthesized in Comparative Example 1 at heating and cooling rates; wherein, (a) is the test curve of the second heating cycle, used to determine the glass transition temperature of the two polyesters; (b) is the test curve of the cooling cycle, used to compare the differences in crystallization behavior of the two polyesters.

[0032] Figure 5 The images show X-ray diffraction patterns of two polyesters in Experimental Example 4 of this invention; where (a) is the XRD pattern of PET synthesized in Comparative Example 1, and (b) is the XRD pattern of PMT synthesized in Example 1, used to compare and analyze the microstructure and crystallinity of the two polyesters.

[0033] Figure 6 The ¹H nuclear magnetic resonance spectra of the degradation solutions of PMT and PET after alkaline hydrolysis in 3.0M NaOH aqueous solution at 90℃ for 5 hours are shown in Experimental Example 7 of this invention. Among them, (a) is the ¹H NMR spectrum of the degradation solution of PMT synthesized in Example 1, and (b) is the ¹H NMR spectrum of the degradation solution of PET synthesized in Comparative Example 1. (a1), (a2), and (a3) ​​are magnified views of the corresponding characteristic regions in Figure (a), and (b1), (b2), and (b3) are magnified views of the corresponding characteristic regions in Figure (b), which are used to analyze the composition and degradation degree of the products of alkaline degradation of the two polyesters.

[0034] Figure 7 The ¹³C nuclear magnetic resonance spectra of the degradation solutions of PMT and PET after alkaline hydrolysis in 3.0M NaOH aqueous solution at 90℃ for 5 hours are shown in Experimental Example 7 of this invention. Among them, (a) is the carbon spectrum of the degradation solution of PMT synthesized in Example 1, and (b) is the carbon spectrum of the degradation solution of PET synthesized in Comparative Example 1. These spectra are used to further verify the chemical structure of the alkaline degradation products of the two polyesters and to compare the difference in degradation efficiency between the two.

[0035] Figure 8 The thermogravimetric analysis (TGA) spectra of PMT and PET in Experimental Example 8 of this invention are shown. (a) shows the thermogravimetric curves of the two polyesters, and (b) shows the differential thermogravimetric curves of the two polyesters, which are used to compare and evaluate the thermal stability and thermal decomposition behavior of the two polyesters. Detailed Implementation

[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0037] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0038] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0039] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0040] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0041] Example 1: Preparation of Polymethyl terephthalate (PMT) This embodiment prepares a biodegradable polyester—polymethyl terephthalate—based on a methylene backbone. The specific preparation steps are as follows: (1) Raw material pretreatment: Terephthalic acid (TPA) was placed in a vacuum drying oven and dried at 60°C for 12 hours; dibromomethane (DBM) was dried and dehydrated using activated molecular sieves; tetramethylammonium hydroxide pentahydrate (TMAH•5H2O) was sealed and stored in an inert atmosphere.

[0042] (2) Polycondensation reaction: In a glove box under an inert atmosphere, 10 g of TMAH•5H2O was added to a four-necked flask. After removing the flask from the glove box, the reaction apparatus was set up, and the temperature was raised to 80°C under nitrogen protection to completely melt TMAH•5H2O. 4.58 g of dried TPA (0.0276 mol) was accurately weighed and added to the flask. Mechanical stirring was started, and the speed was controlled at 100 rpm. The reaction was continued until the TPA was completely dissolved. Then the nitrogen was turned off, and the vacuum pump was turned on to remove the moisture from the system under reduced pressure until the reactants solidified. Nitrogen was reintroduced into the system, and 5.76 g of DBM (0.0331 mol, TPA to DBM molar ratio of 1:1.2), 60 mL of nitrobenzene solvent, and an appropriate amount of triethylbenzylammonium chloride (TEBAC) phase transfer catalyst were added. The reaction temperature was raised to 90°C, and the reaction was stirred at this temperature for 12 hours.

[0043] (3) Product purification: After the reaction was completed, the reaction mixture was slowly poured into 20 times its volume of methanol, and a large amount of white flocculent precipitate was precipitated. The flask was placed in an 8°C refrigerator and allowed to stand for 12 hours to allow the precipitate to precipitate completely. The solid product was collected by vacuum filtration and washed repeatedly with methanol several times to remove residual nitrobenzene, unreacted monomers and byproducts. Finally, the obtained solid was dried under vacuum at 60°C for 72 hours to obtain the target product, polymethyl terephthalate (PMT). The chemical structure of the final obtained polymethyl terephthalate is shown below: .

[0044] Comparative Example 1: Preparation of Traditional Polyethylene Terephthalate (PET) This comparative example is used to compare the performance with Example 1 of the present invention and to prepare a conventional PET polyester control sample. The synthesis method is basically the same as that of Example 1, except that: terephthalic acid (TPA) and 1,2-dibromoethane (EDB) are subjected to a polycondensation reaction at a molar ratio of 1:1.2, the reaction temperature is 120°C, and the reaction time is 24 hours; the obtained product is purified by the same purification steps as in Example 1 to obtain PET polyester.

[0045] Experimental Example 1: Characterization of Chemical Structure by Nuclear Magnetic Resonance Spectroscopy The chemical structures of the PMT prepared in Example 1 and the PET prepared in Comparative Example 1 were characterized by nuclear magnetic resonance spectroscopy. Liquid NMR was used for PET, and solid NMR was used for PMT. The specific methods are as follows: Weigh out 5-10 mg (for use) 1 H-spectrum test) or 40~50mg (for use) 13(C-spectrum testing) The sample was placed in an NMR tube, and 0.5–0.6 mL of deuterated solvent was added to prepare a solution sample. Using a Bruker Ascend 400 NMR spectrometer, the solution sample was collected at various chemical shifts (δ). 1 H and 13 C NMR peak. Before preparing the solution sample, the deuterated solvent was thoroughly dried using molecular sieves; the deuterated solvent used for dibromomethane monomer was deuterated chloroform (CDCl3), the deuterated solvent used for terephthalic acid monomer was deuterated dimethyl sulfoxide (DMSO), and the deuterated solvent used for PET polyester was deuterated trifluoroacetic acid (CF3COOD).

[0046] like Figure 1 As shown in Figure a, the solid-state carbon NMR spectrum of the product synthesized in Example 1 ( 13 The C CP / MASNMR spectrum mainly exhibits four resonance peaks, which are attributed to the C atoms in four different chemical environments within the PMT polyester repeating unit (e.g., C atoms in the four chemical environments of the PMT polyester repeating unit). Figure 1 (As shown in b) No other impurity peaks were clearly observed in the spectrum, indicating that the polymer is a high-purity PMT polyester, and the target product was successfully synthesized.

[0047] Comparative Example 1 Synthesis System 1 H nuclear magnetic resonance spectrum such as Figure 2 As shown, where Figure 2 (a, d) are the monomeric spectra of 1,2-dibromoethane. Figure 2 (b, e) are the monomeric spectra of terephthalic acid. Figure 2 (c,f) are the spectra of the synthesized PET polyester. Figure 2 It can be seen that the polymerization product ( Figure 2 c) 1 Three resonance peaks appeared in the H NMR spectrum, which were attributed to H atoms in two different chemical environments in the repeating unit of PET polyester, and no other impurity peaks were obviously observed in the spectrum.

[0048] Comparative Example 1 Synthesis System 13 C nuclear magnetic resonance spectrum as Figure 3 As shown, where Figure 3 (a, d) are the monomeric spectra of 1,2-dibromoethane. Figure 3 (b, e) are the monomeric spectra of terephthalic acid. Figure 3 (c,f) are the spectra of the synthesized PET polyester. Figure 3 It can be seen that the polymerization product ( Figure 3 c) 13 Four resonance peaks were observed in the C NMR spectrum, which were attributed to C atoms in four different chemical environments within the PET repeating unit, and no other impurity peaks were clearly visible in the spectrum. These results indicate that the polymer synthesized product in Comparative Example 1 is a high-purity PET polyester, and the synthesis of the control sample was successful.

[0049] Experimental Example 2: Determination of Degree of Polymerization by Oxygen Bomb Combustion-Ion Chromatography The number-average degree of polymerization of polyester was determined using bomb ion chromatography. Before testing, the samples were dried in a vacuum oven at 80℃ for 12 hours to remove moisture. The specific testing method is as follows: 300 mg of sample was weighed and placed in an oxygen bomb combustion apparatus, where it was fully combusted and decomposed under high-pressure oxygen atmosphere. During combustion, the bromine in the sample was converted into corresponding inorganic ions, which were absorbed by the absorbent. After combustion was complete, the absorbent was collected and transferred to an ion chromatograph for testing. The bromide ion content was determined using a standard working curve, and the mass fraction of bromine in the sample was then calculated.

[0050] Assuming each polymer molecule chain contains two bromine-terminated groups (double-ended, end-functionality Z=2), the formula for calculating the number-average molecular weight Mn is as follows:

[0051] In the formula: A r This is the atomic weight of bromine. ω is the mass fraction of bromine as determined by ion chromatography; Z represents the end-group functionality of the molecule (Z = 1 for single-end capping and Z = 2 for double-end capping).

[0052] After obtaining the number-average molecular weight, the number-average degree of polymerization Xn is calculated using the following formula:

[0053] In the formula: M0 is the molecular weight of the repeating unit, M end It is the total molecular weight of the terminal groups (excluding the characteristic element portion or the residual mass after deducting bromine).

[0054] The number-average molecular weights and degrees of polymerization of PET and PMT calculated using the above formulas are shown in Table 1. As can be seen from Table 1, the degrees of polymerization of PET and PMT are similar, and their molecular weights are comparable.

[0055] Table 1. Number-average molecular weight and degree of polymerization of PET and PMT

[0056] Experimental Example 3: Determination of Thermal Transition Temperature by Differential Scanning Calorimetry According to the national standard GB / T 19466-2004, the thermal transformation properties of polyester were determined by differential scanning calorimetry. The glass transition temperatures of PMT and PET were compared and tested. The specific method is as follows: Using a Netzsch DSC 214 differential scanning calorimeter, after calibrating the temperature and heat flux with indium standard metal, the test was conducted under a nitrogen atmosphere: 5-10 mg of sample was weighed and sealed in an aluminum crucible placed in the sample chamber, while another blank aluminum crucible was placed in the reference chamber. PMT polyester was tested at 20 °C / min. -1 Under heating and cooling rates, a thermal program of 30℃→220℃→-60℃→220℃ was executed; PET polyester was heated at 20℃•min. -1 At the heating and cooling rates, a thermal program of 30℃→260℃→-60℃→260℃ was executed; the step inflection point temperature of the sample mass normalized heat flux temperature spectrum during the second heating process was taken as the glass transition temperature.

[0057] Test results are as follows Figure 4 As shown, where Figure 4 (a) The DSC curve for the second heating cycle. Figure 4 (b) shows the DSC curve for the cooling cycle. (From...) Figure 4 It can be seen that the glass transition temperatures of PMT and PET are 107℃ and 78℃, respectively, indicating that the PMT molecular chain has higher chain rigidity and the cooperative motion of chain segments is more restricted.

[0058] Experimental Example 4: Determination of Crystallinity by X-ray Diffraction X-ray diffraction was used to characterize the phase composition of the samples, and the differences in microstructure and crystallinity between PMT and PET were compared. The specific testing methods are as follows: Appropriate amounts of PET and PMT samples were taken, ground into powder, and dried in a vacuum drying oven at 60℃ for 24 hours. The powdered samples were then transferred to the grooves of a quartz glass slide, compacted with a metal cylinder, and then the glass slide was fixed to the X-ray diffractometer stage using a clamping device for testing. A copper target was selected as the test target, with a scanning range of 5°~90° and a scanning speed of 10° / min.

[0059] The X-ray diffraction pattern obtained from the test is as follows: Figure 5 As shown, (a) is the XRD pattern of PET and (b) is the XRD pattern of PMT. After integrating the diffraction peaks in the patterns, the crystallinity of PET is calculated to be 41%, while that of PMT is 21%.

[0060] Experiment Example 5: Alkaline Hydrolysis Degradation Experiment A comparative alkaline hydrolysis experiment was conducted on PMT and PET under the same conditions. The specific method is as follows: Weigh 0.5 g of the powder sample and place it in a 250 mL two-necked round-bottom flask (with a mechanical stirrer and a reflux condenser installed at each neck). Add 50 mL of 3.0 M NaOH aqueous solution as a degradation agent and reflux at 50 °C and 300 rpm for 5 h with mechanical stirring. After the reaction is complete, filter the reaction system. Wash the filter residue three times with deionized water and then vacuum dry it at 80 °C for 48 h. Weigh the residue.

[0061] Experimental Example 6: Determination of Degradation Mass Loss Rate The mass loss rate of polyester in the degradation experiment was determined by weighing. The weight loss of PMT and PET after alkaline hydrolysis was estimated by comparison. The weight loss rate (%) of the sample was calculated by the following equation:

[0062] In the formula, m AD (g) represents the sample mass before the alkaline hydrolysis experiment, m PD (g) represents the mass of the dried filter residue after the alkaline hydrolysis experiment.

[0063] The test results are shown in Table 2. Under the conditions of 3.0M NaOH aqueous solution and reaction at 50℃ for 5h, the mass loss rates of PET polyester and PMT were 23.7% and 98.1%, respectively, indicating that the alkaline degradation efficiency of PMT is significantly higher than that of traditional PET.

[0064] Table 2 Comparison of mass loss rates of PMT and PET in alkaline hydrolysis experiments

[0065] Chemical structure characterization of degradation products in Experiment Example 7 The degradation product solution was analyzed using 1H and 1C NMR spectra using a Bruker Ascend 400 NMR spectrometer to determine its composition. The sample preparation method for NMR spectroscopy of the degradation solution was as follows: 0.1 mL of the degradation solution was placed in an NMR tube, 0.6 mL of heavy water was added, and the tube was sealed before testing.

[0066] The degradation solution after 5 hours of alkaline hydrolysis 1 H nuclear magnetic resonance spectrum such as Figure 6 As shown, (a) is the spectrum of PMT degradation solution, (b) is the spectrum of PET degradation solution, and (a1,a2,a3) and (b1,b2,b3) are magnified views of the corresponding spectra. Figure 6 It can be seen that PMT degradation solutions contain δ values ​​of 7.79, 8.37, and 3.26. 1 The H resonance peaks were attributed to the hydrogen atoms at the 2 and 3 carbon positions of the benzene ring in sodium terephthalate, the formate proton peak generated by the conversion of formaldehyde in a strongly alkaline aqueous solution, and the methanol proton peak, respectively; while only δ=7.80ppm was observed in the PET degradation solution. 1The H resonance peak is attributed to the hydrogen on the 2,3 carbons of the benzene ring in sodium terephthalate, and its peak intensity is much lower than that of the PMT degradation solution.

[0067] The degradation solution after 5 hours of alkaline hydrolysis 13 C nuclear magnetic resonance spectrum as Figure 7 As shown, (a) is the degradation spectrum of PMT and (b) is the degradation spectrum of PET. Figure 7 It can be seen that the PMT degradation solution contained δ values ​​of 175.19, 138.53, 128.50, and 48.76 ppm. 13 The C resonance peaks are attributed to the carbonyl carbon, carbons at positions 1 and 4 of the benzene ring, carbons at positions 2 and 3 of the benzene ring, and methyl carbon of sodium terephthalate, respectively; while the PET degradation liquid only shows a resonance peak with a very low signal-to-noise ratio of δ=128.62ppm, which is attributed to the carbons at positions 2 and 3 of the benzene ring of sodium terephthalate.

[0068] The above spectral data show that the concentration of hydrolysis products in the PMT degradation solution is much higher than that in the PET degradation solution, and the alkaline degradation efficiency of PMT is significantly better than that of traditional PET polyester.

[0069] Example 8: Characterization of thermal stability by thermogravimetric analysis Thermogravimetric analysis of PMT and PET polyester was performed using a TA Instruments SDT Q600 thermogravimetric analyzer to evaluate their thermal stability. Tests were conducted at 20 mL / min. -1 The procedure is carried out under a nitrogen atmosphere, and the specific method is as follows: Two empty Al2O3 crucibles were placed on the two pans of a balance inside the furnace and leveled. 3-5 mg of dried polyester sample was weighed and placed in the outer crucible. The furnace was then closed. The furnace was opened at 10 °C / min. -1 The temperature was increased from room temperature to 800℃, and the weight of the sample and the rate of weight change with temperature were recorded in real time. The temperature at which the weight loss was 5% was defined as the thermal decomposition temperature.

[0070] The thermogravimetric analysis curves obtained from the test are as follows: Figure 8 As shown, (a) is the thermogravimetric curve and (b) is the differential thermogravimetric curve. Figure 8 It is known that the 5% thermal decomposition temperatures of PMT and PET are 305.2℃ and 363.7℃, respectively, indicating that traditional PET has better initial thermal stability than PMT. Meanwhile, the thermal decomposition of PMT exhibits a clear two-step decomposition stage: the first stage involves heterolytic cleavage of the –OCH2O– structure in the main chain, releasing formaldehyde; after the first stage of cleavage, the remaining structural rigidity of the remaining groups is high, requiring higher temperatures for further cleavage. Compared to PET, PMT has a lower initial decomposition temperature and more significant stepwise pyrolysis characteristics, resulting in a slight decrease in thermal stability, but it still meets the basic usage requirements for general-purpose plastics and fiber materials.

[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A biodegradable polyethylene terephthalate, characterized in that, The repeating unit of the polymethyl terephthalate is composed of terephthalic acid structural units and methylene groups connected by ester bonds, and the main molecular chain contains -O-CH2-O-methyldiester structural units.

2. The biodegradable polyethylene terephthalate according to claim 1, characterized in that, The number-average degree of polymerization of the poly(methyl terephthalate) is 11-14.

3. A method for preparing the biodegradable polyethylene terephthalate according to claim 1, characterized in that, This includes the step of carrying out a solution polycondensation reaction of terephthalic acid and dibromomethane in an organic solvent under the combined action of an alkaline catalyst and a phase transfer catalyst.

4. The preparation method according to claim 3, characterized in that, Specifically, the steps include the following: (1) Heat the temperature to 80°C to melt the alkaline catalyst, and add terephthalic acid to react; (2) Add dibromomethane, organic solvent and phase transfer catalyst, and carry out polycondensation reaction at 90~120℃ under inert atmosphere and mechanical stirring for 12~24 hours; (3) After the reaction is complete, the reaction solution is added to a settling agent to precipitate the precipitate. After filtration, washing and drying, the target product is obtained.

5. The preparation method according to claim 4, characterized in that, In step (1), the molar ratio of terephthalic acid to alkaline catalyst is 1:(2.0~2.2), and the alkaline catalyst is tetramethylammonium hydroxide pentahydrate; in step (2), the molar ratio of terephthalic acid, dibromomethane, and phase transfer catalyst is 1:(1.0~1.5):(0.05~0.2), and the phase transfer catalyst is triethylbenzylammonium chloride or tetrabutylammonium bromide, and the organic solvent is nitrobenzene; in step (3), the settling agent is methanol, ethanol, or an aqueous solution thereof.

6. An application of the biodegradable polyethylene terephthalate according to claim 1, characterized in that, The applications include utilizing the acid-base degradable properties of the polymethyl terephthalate to prepare it into degradable polymer products, or achieving the harmless disposal and component recovery of materials containing the polymethyl terephthalate through degradation treatment.

7. The application according to claim 6, characterized in that, The biodegradable polymer products include disposable packaging materials, biodegradable fibers, and agricultural films.

8. The application according to claim 6, characterized in that, The polymethyl terephthalate is used as a biodegradable matrix resin in the composite material. By degrading the matrix resin, the functional components in the composite material can be recovered without damage.

9. The application according to claim 8, characterized in that, The degradation treatment is carried out in an alkaline environment; the alkaline environment is an aqueous solution of sodium hydroxide or potassium hydroxide with a concentration of 0.5~5.0M, and the degradation temperature is 25~100℃.

10. The application according to claim 8, characterized in that, The functional components recovered in the composite material are reinforcing fibers or fillers.